Constructing Digital Democracies: Facebook, Arendt, and the Politics of Design. (February 2021) - Forestal, Jennifer
Deliberative democracy requires both equality and difference, with structures that organize a cohesive public while still accommodating the unique perspectives of each participant. While institutions like laws and norms can help to provide this balance, the built environment also plays a role supporting democratic politics—both on- and off-line. In this article, I use the work of Hannah Arendt to articulate two characteristics the built environment needs to support democratic politics: it must (1) serves as a common world, drawing users together and emphasizing their common interests and must also (2) preserve spaces of appearance, accommodating diverse perspectives and inviting disagreement. I, then, turn to the example of Facebook to show how these characteristics can be used as criteria for evaluating how well a particular digital platform supports democratic politics and providing alternative mechanisms these sites might use to fulfill their role as a public realm.